PENCEGAHAN PERMAINAN "STARTER"MELALUI PENDEKATAN PERSONAL SAFETY SKILL PADA MURID SEKOLAH DASAR - Handayani, Trini (JE (Journal of Empowerment), 2017)
Starter is a game made by boys, especially in children at the elementary level. This game often effects on victim. The victims and perpetrators are not aware of the occurrences impact of this game, that are, the infection of the testicles, testicular organ damage, and even infertility. Game starter can be categorized as a form of sexual violence, because it is directly related to the primary reproductive organs. One of the preventive efforts undertaken is to teach personal safety skills to children. This method is popularized by Bagley and King in 2004. Personal Safety Skills is a skill that must be understood by children, so that they can avoid violent offenders sexual and situations that allow sexual violence.Â